LANDSLIDE DISASTER MITIGATION POLICY IMPLEMENTATION IN THE REJANG LEBONG REGENCY, BENGKULU PROVINCE - Putrianto, Leoni Indah; Nur, Utami; Husein, Rahmawati (Jurnal Pemerintahan Dan Keamanan Publik (JP dan KP), 2024)
This research aims to examine the implementation of structural landslide disaster mitigation policies in Rejang Lebong Regency. The study is qualitative descriptive research, with data collection carried out through observation. The data analysis technique involves data reduction, data presentation, and drawing conclusions. The findings show that the implementation of landslide disaster mitigation policies in Rejang Lebong Regency has been carried out according to the targets set by the Head of the Agency in the performance agreement, which each relevant sector must implement. However, these targets have not been fully achieved. Despite coordination among agencies to meet the policy goals and evaluation through the Government Agency Performance Report, implementing the landslide mitigation policy has not yet reached optimal results. Therefore, it can be concluded that the implementationof landslide disaster mitigation policies in Rejang Lebong Regency has not been maximized. Keywords: Policy Implementation, Mitigation, Landslides.